Gender Influence on the Effects of Study Skills and Self- Reinforcement Counselling on the Study Behaviour of College of Education Students in Ghana - Amuaful, Gladys Abena; Awabil, Godwin; Eyiah-Bediako, Sylvia (Journal of Education and Practice, 2025)
Purpose: The study examined the gender influence on the effects of study skills and self -reinforcement counselling on the study behaviour of College of Education students (CoE) in Ghana Methodology: Quasi-experimental design with a control group that was tested before and after the study's main group was used for the study with sixty (60) participants used surveyed for this study. The instrument used in the pre-test-post-test was a structured questionnaire known as Study Behaviour Inventory (SBI) which was adapted from the Study Habit Survey (SHS) form B developed by Essuman (2006). Data were analysed using descriptive statistics (means and standard deviation) and inferential statistics (two-way analysis of covariance (ANCOVA) one-way multivariate analysis of covariance (MANCOVA). Findings: The study revealed that male and female participants did not respond differently to either study skills counselling or self-reinforcement counselling. That is gender of students do not determine their study behaviour when exposed to study skills and self-reinforcement counselling interventions. Again, study revealed that study skills counselling and self-reinforcement counselling have significant effects on the study behaviour of students with regard to time management, concentration, consultation, note taking, reading and library use skills. Unique contribution to theory, practice and policy: the study recommended to counselling coordinators and management of the various colleges to ensure that study skills and self-reinforcement counselling interventions are regularly provided as (considered) intervention tools for improving the five (5) dimensions of study behaviour of College of Education students in Ghana irrespective of their gender.